Suara “Merah” Ibu Kota: Geliat Politik Partai Komunis Indonesia Comite Djakarta Raya - Satriono Priyo Utomo (Lembaran Sejarah, 2016)
After the rise of nationalist movement, the Indonesian Communist Party (PKI) was one of the disciplined organizations in Indonesia. PKI has become the primary example in understanding how organized movements transformed after Indonesia’s independence. Ruth McVey’s assessment that the PKI as being the most organized organization is not excessive. When the PKI was revamped in the early 1950, it conducted political education through translation and publication work. In various cities they conducted research in order to understand the social contexts to determine the party’s political programs. In various cities they did research that had a purpose to understand the social context in order to determine the party’s political program, including one of the important areas was Jakarta. Politic contestation in Jakarta was not always interpreted with the struggle for mastery hegemonic discourse. Although in the period of 1950-1965 the discourse struggle was involved the three big powers, nationalists, Islamist and communists. This idea was just organized by chief of these organizations that was located in Jakarta. In addition, Jakarta has major problems in meeting the everyday needs of its population. Thus, the existence of PKI in Jakarta does not always play practical issues, but also advocated populist issues as well.